Current Status of Chinese Medical Students’ Professional Identity After COVID-19 and the Factors That Influence It - Lai, Tinghong; Liang, Weidong; Zhong, Maolin; Zhu, Pingping; Li, Bin (Frontiers in Psychology, 2022)
Objective: To understand the current situation regarding medical students’ professional identity after COVID-19, as well as the factors that influence it. The purpose of this is to reform departmental teaching and promote the development of medical education. Methods: A questionnaire examining medical students’ professional identity that was compiled by Fujian Medical University and a questionnaire designed by the researchers were used. Results: It was found that the professional identity of medical students was upper middle level. The professional attitude of medical students was generally positive. The scores for boys were higher than girls in terms of value (t=2.057, P<0.05), whereas the scores for girls where higher than those for boys when it came to aspects such as professional environment (t=-3.918, P<0.001) and professional cognition (t=-3.855, P<0.001). There was a significant difference in the sense of professional identity between people with and without siblings (t =2.264, P<0.05); The scores of students who participated in prevention and control of the epidemic were significantly higher than those who did not (t=2.267, P<0.01). Professional identity decreased gradually in related to better grades, but it increased at the graduate stage; the grade differences were significant (F=10.302, P<0.001). The difference between majors was significant (F=5.718, P < 0.01). Factors such as family members’ influence, attitude towards occupation, grades, major, registered residence, and college choosing were the main factors that influenced medical students’ professional identity. Conclusions: Medical students’ professional identity needs to be improved. There should be increased education regarding professional development and career planning.